Medicinal Properties of Illicium Verum Hook. F. - Shagufta Khan; Asra Khan Pahore; Nasim Karim (JLUMHS)
Medicinal plants have active elements that can be used for cures or making drug precursors. According to the World Health Organization, 80% of the world's population depends on these plants as traditional treatments to meet their health care needs. Illicium verum Hook. F. (star anise) is an extensively used spice in traditional Chinese cuisine as a flavoring agent or a historical medicine for vomiting, stomachache, flatulence, and rheumatism and is included in the Chinese Pharmacopoeia. Some active components of star anise are essential oil, anethole, trans-anethole, sesquiterpenoids, shikimic acid, lignans, etc., which possess anxiolytic, neuro-protective, antibacterial, antifungal, anti-inflammatory, antiemetic, anti-flu, antidiarrheal, antispasmodic, anti-diabetic, antioxidant, anti-thrombotic, and anti-tumour effects that are discussed in this review article.